PLASTID GENOME SEQUENCING OF TULIPA SPECIES FROM KAZAKHSTAN: INSIGHTS INTO GENOMIC STRUCTURE, REPEATS, NUCLEOTIDE DIVERSITY, AND PHYLOGENETIC RELATIONSHIPS - Almerekova, S.; Yermagambetova, M.; Ivaschenko, A.; Turuspekov, Y.; Abugalieva, S. (Eurasian Journal of Applied Biotechnology, 2024)
We sequenced and analyzed the plastid genomes of Tulipa species using the Illumina NovaSeq 6000 platform. The plastomes exhibited a typical quadripartite structure with LSC, SSC, and IR regions, displaying a GC content ranging from 36.63% to 36.69%. Gene annotation revealed 136 genes across all species, including 80 protein-coding, 30 tRNA, and 4 rRNA genes. Repeat sequence analysis identified simple sequence repeats, predominantly mononucleotide repeats, and long repeat types, with palindromic repeats being the most abundant. Nucleotide diversity analysis indicated protein-coding genes with high variability. Phylogenetic analysis based on nucleotide sequences of complete plastid genomes grouped the species into three main clades corresponding to Tulipa subgenera. This study provides insights into the plastid genome structure, repeat sequences, and phylogenetic relationships in Tulipa, highlighting the potential of the ycf1 gene as a DNA barcode for Tulipa species. This research was funded by the Science Committee of the Ministry of Education and Science of the Republic of Kazakhstan (Grant No. AP14870612).